Interação entre as paredes de alvenaria estrutural - Pascoal, Paula Taiane (2016)
The present work approaches a study about the interaction between walls on structural masonry buildings of concrete blocks submitted to vertical forces. The goal consists in to make a numerical analyses of the interaction of structural masonry submitted to vertical forces for different positions of walls in buildings, but with the same load nature, high and proprieties of the constituent materials. Were made analysis in three buildings and in each one of them, were evaluated three walls, taking in consideration the resultants of the grouped floors and isolated floors. For this were used the constructive phasing routine of the SAP2000 V12 software, that uses the method of finite elements. The loads in the base of the ground floors walls of the three buildings vary in a not uniform way and the adoption of a single value as interaction rate can result in not realistic loads in some situations.